2013
DOI: 10.1111/jam.12328
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, characterization and mode of antimicrobial action againstVibrio choleraeof methyl gallate isolated fromAcacia farnesiana

Abstract: Aims: The antimicrobial activity of Acacia farnesiana against Vibrio cholerae has been demonstrated; however, no information regarding its active compound or its mechanism of action has been documented. Methods and Results: The active compound was isolated from A. farnesiana by bioassay-guided fractionation and identified as methyl gallate by nuclear magnetic resonance (NMR) techniques ( 1 H NMR and 13 C NMR). The minimum bactericidal concentration (MBC) of methyl gallate and its effect on membrane integrity, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
35
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(36 citation statements)
references
References 46 publications
1
35
0
Order By: Relevance
“…The inicial steps of development of degenerative diseases are preventing by protection of target molecules as lipids, proteins and nucleic acids from oxidative damage [ 2 ]. Many plants distributed in arid and semi-arid environments have alternative uses such as forage resources; traditional medicine and more recently, they have been pointed out as antioxidant sources [ 3 5 ], mainly due to their polyphenol content. These compounds have received attention because of their antioxidant capabilities and their protection against ROS-induced damage [ 2 , 6 ] with biological functions like antiinflammatory, anticancer, antiobesity, antiaging [ 7 ], hepatoprotective and antidiabetic properties [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The inicial steps of development of degenerative diseases are preventing by protection of target molecules as lipids, proteins and nucleic acids from oxidative damage [ 2 ]. Many plants distributed in arid and semi-arid environments have alternative uses such as forage resources; traditional medicine and more recently, they have been pointed out as antioxidant sources [ 3 5 ], mainly due to their polyphenol content. These compounds have received attention because of their antioxidant capabilities and their protection against ROS-induced damage [ 2 , 6 ] with biological functions like antiinflammatory, anticancer, antiobesity, antiaging [ 7 ], hepatoprotective and antidiabetic properties [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Acacia species are widely distributed in arid, semiarid and tropical regions of Mexico and all around the world. The extracts obtained from these plants have previously shown antimicrobial [ 3 ], antihelmintic [ 9 ] and antioxidant [ 4 ] properties.…”
Section: Introductionmentioning
confidence: 99%
“…[38], 4-methoxybenzoic acid(8) [39], 3-hydroxy-1-(3,5-dimethoxy-4-hydroxyphenyl)propan-1-one(9) [40], 3-hydroxy-1-(4-hydroxy-3-ethoxyphenyl) propan-1-one (10)[41], 2,3-dihydroxy-1-(4-hydroxy-3-methoxyphenyl)propan-1-one (11)[41], and (2S,3R)-4E-dehydrochebulic acid trimethyl ester (12)[42], a mixture of cerebrosides: gynuramides I-IV(13)(14)(15)(16) [43], three coumarins: scopoletin (17)[44], fraxetin (18)[45], and 6-hydroxy-5,7dimethoxycoumarin (19)[46], six coumarinolignans: cleomiscosins A-D (20-23)[47][48][49], malloapelin A (24)[32,33], and malloapelin B (25)[32,33], three diterpenes: ent-11-α-hydroxy-3-oxo-13-epi-manoyl oxide(26)[50], excoecafolin D (27) [15], and agallochin I (28) [51], two flavonoids: (+)-catechin (29) [52] and kaempferol-3-O-β-d-glucoside (30) [53], six steroids: 6 -(stigmast-5-en-7-one-3-O-β-glucopyransidyl) hexadecanoate (31) [54], (6 -O-palmitoyl) sitosterol-3-O-β-d-glucoside (32) [26], a mixture of βsitosterol (33) and stigmasterol (34) [55], a mixture of 3-O-β-d-glucopyranosyl β-sitosterol (35) and 3-O-β-d-glucopyranosyl stigmasterol (36) [56], and eight galloyl glucoses: isopropyl O-β-(6 -O-galloyl) glucopyranoside (37) [57], 4-hydroxy-3-methoxyphenol 1-O-β-d-(2 ,6 -di-O-galloyl)glucoside (38) [58], 3-methoxy-4-hydroxyphenyl 1-O-β-d-(6 -O-galloyl)glucopyranoside (39) [59], 1,2,3,4,6-penta-O-galloylβ-d-glucose (40) [60], corilagin (41) [61], 1,4,6-tri-O-galloyl-β-d-glucose (42) [62], 1,3,6-tri-O-galloyl-β-dglucose (43) [63], and gallic acid 4-O-β-d-(6 -O-galloyl)-glucose (44) [64]. The phytochemical data of known compounds are available in Supplementary Materials.…”
mentioning
confidence: 99%
“…A. farnesiana is one of the medicinally important plants of Ayurvedic system of medicine and has been used for various pharmacological activities such as Vibrio cholera inhibition [11], herbicide [12], antimalarial [13], antioxidant [14], antidiarrheal [15], antimicrobial [16], phytoremediation [17], defluoridation, adsorbent [18], antiulcer [19], acetylcholine esterase, NADH oxidase inhibitory [20], bronchodilator [21], and anti-inflammatory [22]. The compounds, viz., lectin-like protein, cyclopropenoid fatty acids [23], four new diterpenes, acasiane A, acasiane B, farnesirane A, and farnesirane B [24], methyl gallate [25], naringenin, kaempferol, quercetin, and myricetin [26] have been isolated from various parts of the plant. In view of the above fact and literature survey revealed that phytochemicals present in A. farnesiana pod are active against many pharmacological activities, but so far no investigation on its antiproliferative potential has been made.…”
Section: Introductionmentioning
confidence: 99%